2016
DOI: 10.1021/acs.biochem.6b00625
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis Reveals the Multifactorial Mechanism of Histone H3 Clipping by Chicken Liver Histone H3 Protease

Abstract: Proteolytic clipping of histone H3 has been identified in many organisms. Despite several studies, the mechanism of clipping, the substrate specificity, and the significance of this poorly understood epigenetic mechanism are not clear. We have previously reported histone H3 specific proteolytic clipping and a protein inhibitor in chicken liver. However, the sites of clipping are still not known very well. In this study, we attempt to identify clipping sites in histone H3 and to determine the mechanism of inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Proteases play regulatory roles in epigenetic mechanisms of altered gene expression. Various non-specific and N-tail specific histone proteases are thought to assist in fertilization, histone turnover, gene de-repression, histone removal during spermatogenesis, and reversal of N-tail methylation [86]. In N-tail clipped histone H3, lysines for acetylation have been removed, which may result in transcriptionally inactive chromatin.…”
Section: Proteases and Diseasementioning
confidence: 99%
“…Proteases play regulatory roles in epigenetic mechanisms of altered gene expression. Various non-specific and N-tail specific histone proteases are thought to assist in fertilization, histone turnover, gene de-repression, histone removal during spermatogenesis, and reversal of N-tail methylation [86]. In N-tail clipped histone H3, lysines for acetylation have been removed, which may result in transcriptionally inactive chromatin.…”
Section: Proteases and Diseasementioning
confidence: 99%
“…Within the cell, CSTB localizes to the nucleus and the cytosol, where it is associated with a subset of lysosomes (Riccio et al, 2001;Brännvall et al, 2003;Alakurtti et al, 2005). In the nucleus, CSTB interacts with cathepsin L (Ceru et al, 2010;Chauhan et al, 2016), a protease with several reported nuclear functions including regulation of cell cycle progression through proteolytic processing of CDP/Cux transcription factor, stabilization of epigenetic heterochromatin markers, sperm histone degradation, and histone H3 tail clipping (Goulet et al, 2004;Bulynko et al, 2006;Duncan et al, 2008;Adams-Cioaba et al, 2011;Morin et al, 2012). Cathepsin L is one of several intracellular proteases that have emerged as epigenetic regulators through their ability to remove histone tails, particularly during cell-state transitions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“… 4 The mouse H3t histone has a human counterpart, H3T (H3.4), and shares a common chaperon recognition motif with H3.1 and H3.2. 5 Knockout mice for H3t were first generated in 2017; both male and female H3t null mice were viable and healthy, but the male mice were sterile. 6 H3t deficiency leads to azoospermia because of the loss of haploid germ cells.…”
mentioning
confidence: 99%